TRANSFORMASI DIGITAL DAN KINERJA PERUSAHAAN TELEKOMUNIKASI: BUKTI EMPIRIS DI INDONESIA - Sulbahri , Rifani Akbar; Putri, Yuni Adinda (Jurnal Keuangan dan Bisnis, 2025)
Abstract (Times New Roman 11) Purpose - This study aims to examine the impact of digital transformation—including the adoption of 5G technology, cloud computing, and the Internet of Things (IoT)—on the performance of telecommunication companies in Indonesia. The research focuses on assessing how digitalization influences financial and operational performance, with government policy considered as a moderating factor. Design/Methodology/Approach - A quantitative, causal research design was employed. Data were collected through surveys, interviews, and documentation from five major Indonesian telecommunication firms during the 2023–2024 period. Multiple linear regression analysis was conducted using SPSS software to determine the effect of digital technology adoption on company performance. Findings - The results indicate that digitalization significantly enhances corporate performance in terms of financial outcomes and operational efficiency. The implementation of 5G and cloud computing strengthens service quality and customer satisfaction, while government regulation plays a moderating role in these effects. Practical Implications - These findings offer practical implications for policymakers and telecom executives in formulating digital strategies aligned with regulatory frameworks and market needs. The study also informs public policy aimed at accelerating equitable digital infrastructure across underserved regions. Originality/Value - This research provides novel insights by addressing literature gaps concerning digital transformation in emerging economies. Its originality lies in integrating technology adoption, firm performance, and regulatory influence—an approach rarely explored in previous studies within the Indonesian telecom sector. Keywords: 5G Technology; Cloud Computing; Digital Transformation; Firm Performance; Regulation